2006
DOI: 10.1080/13880200600794063
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Antioxidant Compounds Produced byin Vitro. Cultures of Rosemary (Rosmarinus officinalis.) and Their Anti-inflammatory Effect on Lipopolysaccharide-Activated Microglia

Abstract: Different culture types (shoot culture, callus culture, and cell suspension culture) of Rosmarinus officinalis L. were established and their ability to biosynthesize the phytochemicals carnosic acid, carnosol, and rosmarinic acid were assessed and compared with subcultures of the same stem plant over time. Furthermore, we examined the antioxidative effect of extracts from different culture types by measuring their scavenging activity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals as well as their anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…Kuhlmann and Röhl [70] compared the phenolic content using HPLC-DAD and the antioxidant capacity with DPPH of different in vitro culture types, namely shoot culture, callus culture and cell suspension of Rosmarinus officinalis. The dominant compounds found were diterpenes (carnosic acid and carnosol) and depside (rosmarinic acid).…”
Section: Discussionmentioning
confidence: 99%
“…Kuhlmann and Röhl [70] compared the phenolic content using HPLC-DAD and the antioxidant capacity with DPPH of different in vitro culture types, namely shoot culture, callus culture and cell suspension of Rosmarinus officinalis. The dominant compounds found were diterpenes (carnosic acid and carnosol) and depside (rosmarinic acid).…”
Section: Discussionmentioning
confidence: 99%
“…Flat, well attached, nonstellate-shaped microglia were considered as quiescent (Röhl and Sievers 2005), if no NO release into the culture medium could be measured by means of the Griess assay. Then, stimulation with 0.02 lg/ml lipopolysaccharides (LPS, L-8274, Sigma) in 310 ll/cm 2 growth medium was performed for 24 h. Previously, we have shown that this concentration induces an increased microglial mRNA expression of IL-6 (130-fold), IL-1b (60-fold), TNF-a (3-fold), iNOS (200-fold) and COX-2 (14-fold) (Röhl et al 2007) and a maximal LPSinduced NO production in our microglial cell cultures (Kuhlmann and Röhl 2006) but not in purified astroglial cultures (Röhl and Sievers 2005).…”
Section: Microglial Cultures and Microglia-conditioned Mediummentioning
confidence: 97%
“…Moreover, both microglia and astrocytes have been shown to be highly regulated in AD brains [ 133 , 134 ]. The potent anti-inflammatory activity of rosemary diterpenes in both the microglial cells [ 126 , 135 ] and other inflammatory models therefore suggests their potential in tackling AD.…”
Section: Pharmacological Targets Of Rosemary Diterpenes Related Tomentioning
confidence: 99%